Trilled sounds in Brazilian Portuguese: Phonetic and phonological characterization - Hoyos-Andrade, R. E. (Presses Univ France, 2002)
This paper deals with the phonological definition of trills in Brazilian Portuguese. The phonemic existence of two distinctive R's, one soft the other strong, is taken for granted. After reviewing the ideas of some Portuguese-speaking phoneticians on this matter, 146 occurrences of R's - recorded by two informants - were acoustically analyzed, the formants' general aspect and the length of the R segments were studied in the resulting spectrograms. The phonological table displayed in the conclusion does not include any trill. The soft phoneme /r/, instead, is classified as an interrupted apico-alveolar tap with a retroflex allophone. Naturalization between these two units is discarded.t